The clinical features that contribute to poor bone health in young Australians living with cystic fibrosis: A recommendation for BMD screening. Issue 7 (1st April 2021) - Atlas, Gabby; Yap, Matthew; Lim, Angelina; Vidmar, Suzanna; Smith, Nathan; King, Louise; Jones, Alicia; Hong, Jason; Ranganathan, Sarath; Simm, Peter J.
Abstract: Background: For Australians living with cystic fibrosis (CF), increased longevity means greater consideration needs to be given to long‐term endocrine sequelae such as CF‐related bone disease. Deficits in bone mass accrual are most likely to occur during childhood and adolescence. Current guidelines in Australia suggest repeat dual‐energy X‐ray absorptiometry (DXA) scans every 2 years. This study aims to stratify clinical factors that determine future bone health in the Australian CF population and use this to guide a more streamlined approach to bone health screening. Methods: This study was a retrospective audit of all patients diagnosed with CF who were treated at the Royal Children's Hospital Melbourne, Australia from 2000 to 2016 ( n = 453). Two hundred and two patients had a DXA scan in the study period (191 with height‐adjusted data) and 111 patients had more than one scan (108 with height‐adjusted data). An investigation into the associations between bone mineral density (BMD) Z score and potential risk factors was conducted using DXA and historical data. Results: The main predictor of future BMD was the previous BMD Z score ( p < .001). Other factors found to be determinants of BMD included nutritional status, lung function (FEV1 ), age, history of previous fracture, oral corticosteroid use, and the number of hospital admissions. However, after adjusting for previous BMD, evidence of an association remained only with nutritional status, FEV1, and number of hospital admissions. Conclusion: Second yearly scans may be unnecessary in children with an adequate DXA score on the initial scan who remain clinically stable. However, clinical deterioration in those whose BMD was previously normal, may require closer monitoring of bone health. We propose a guideline for the frequency of DXA monitoring in relation to clinical risk factors.